2017
DOI: 10.1021/acs.jafc.7b00497
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contribution of Fish Feed and Phytoplankton to the Content of Volatile Terpenes in Cultured Pangasius (Pangasianodon hypophthalmus) and Tilapia (Oreochromis niloticus)

Abstract: Geosmin and 2-methylisoborneol are the most recognized off-flavors in freshwater fish, but terpenes may also contribute off-flavor in fish. We identified six monoterpenes, 11 sesquiterpenes, and three terpene-related compounds in pangasius and tilapia from aquaculture farms in Bangladesh. The concentrations of most of the volatiles were below published odor thresholds, except for α-pinene, limonene, β-caryophyllene, α-humulene, and β-ionone in tilapia, and limonene and β-ionone in pangasius. To identify source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 41 publications
2
43
0
4
Order By: Relevance
“…Then the volatile stock solutions were added to the MPs (5 mg mL −1 ) or control solution (0.6 mol L −1 NaCl and 10 mmol L −1 Tris–HCl, pH 7.2) and blended thoroughly with a vortex mixer, resulting in an ultimate concentration of 1 mL L −1 for each volatile compound. The four aldehydes were selected because of their contributions to the odor of grass carp and other freshwater fish . Subsequently, 10 mL of mixture was loaded into a 20 mL headspace vial and sealed with a PTFE/silicone septum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the volatile stock solutions were added to the MPs (5 mg mL −1 ) or control solution (0.6 mol L −1 NaCl and 10 mmol L −1 Tris–HCl, pH 7.2) and blended thoroughly with a vortex mixer, resulting in an ultimate concentration of 1 mL L −1 for each volatile compound. The four aldehydes were selected because of their contributions to the odor of grass carp and other freshwater fish . Subsequently, 10 mL of mixture was loaded into a 20 mL headspace vial and sealed with a PTFE/silicone septum.…”
Section: Methodsmentioning
confidence: 99%
“…However, the presence of fishy and earthy‐musty odors has always been a problem that has seriously restricted the development of the freshwater surimi production industry . Numerous researches have reported that aldehydes are key fishy volatile flavor compounds in fish and fish products and well known to be generated from lipolysis or oxidation …”
Section: Introductionmentioning
confidence: 99%
“…Besides preharvest off‐flavours, off‐flavours can also originate from lipid oxidation or bacterial spoilage associated with improper post‐harvest handling and storage (Flick & Martin, ; Flick, Hong, & Knobl, ). Podduturi et al () suggested that terpenes in fish feed and phytoplankton can be sources of GSM, MIB and other terpenes, contributing to the off‐flavour in fish flesh. However, off‐flavours of dietary origin are only rarely detected in aquaculture (Tucker, ).…”
Section: Origin Of Off‐flavoursmentioning
confidence: 99%
“…In addition to GSM and MIB, about 20 other compounds responsible for a musty off‐flavour in water or beverages have been identified, including several alkyl‐methoxypyrazines, 1‐octen‐3‐ol, 1‐octen‐3‐one, trans‐octenol, 3‐octanone, fenchol, fenchone and chloroanisoles (Callejón, Ubeda, Ríos‐Reina, Morales, & Troncoso, ). Additionally, aldehydes, alcohols (e.g., 1‐octen‐3‐ol, imparting a mushroom odour) and terpenes (e.g., L‐α‐terpineol, and farnesol imparting flowery and earthy flavours, respectively) have been detected in fish flesh, influencing its taste and flavour (Podduturi, Petersen, Mahmud, Rahman, & Jørgensen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Terpenes exert diverse medicinal effects. 55, [63][64][65][66][67][68][69][70][71][72][73][74][75] Terpenoids are also flavor and fragrance components common to human and pet diets and are considered by the US FDA to be generally recognized as safe (GRAS). The use of terpenoids in food-producing animal feed is being researched due to biotechnological effects on food quality and safety as well as for performance enhancement such as weight gain; feed conversion rate; nutrient absorption; gutlining morphology; relief of intestinal immune defense in gut-associated lymphoid tissue due to antibacterial, antiviral, antifungal properties; intestinal microbiota health; meat lipid oxidation; milk composition; malodors and off-flavor in aquaculture; and palatability of feed.…”
Section: Cannabis Medicinal Profile and Phytoconstituentsmentioning
confidence: 99%